Harnessing genetic resistance to rusts in wheat and integrated rust management methods to develop more durable resistant cultivars - Mapuranga, Johannes; Zhang, Na; Zhang, Lirong; Liu, Wenze; Chang, Jiaying; Yang, Wenxiang (Frontiers in Plant Science, 2022)
Wheat is one of the most important staple foods on earth. Leaf rust, stem rust and stripe rust, caused by Puccini triticina, Puccinia f. sp. graminis and Puccinia f. sp. striiformis, respectively, continue to threaten wheat production worldwide. Utilization of resistant cultivars is the most effective and chemical-free strategy to control rust diseases. Convectional and molecular biology techniques identified more than 200 resistance genes and their associated markers from common wheat and wheat wild relatives, which can be used by breeders in resistance breeding programmes. However, there is continuous emergence of new races of rust pathogens with novel degrees of virulence, thus rendering wheat resistance genes ineffective. An integration of genomic selection, genome editing, molecular breeding and marker-assisted selection, and phenotypic evaluations is required in developing high quality wheat varieties with resistance to multiple pathogens. Although host genotype resistance and application of fungicides are the most generally utilized approaches for controlling wheat rusts, effective agronomic methods are required to reduce disease management costs and increase wheat production sustainability. This review gives a critical overview of the current knowledge of rust resistance, particularly race-specific and non-race specific resistance, the role of pathogenesis-related proteins, non-coding RNAs, and transcription factors in rust resistance, and the molecular basis of interactions between wheat and rust pathogens. It will also discuss the new advances on how integrated rust management methods can assist in developing more durable resistant cultivars in these pathosystems.